Ultrasound diagnostics of knee joint diseases - Yodgoraliev H.H; Zulunov A.T; Rashidova Sh.U. (Zien Journals, 2023)
This article highlights a study dedicated to improving ultrasound diagnostics in diseases of the knee joint and increasing the information content of the ultrasound method
Keywords: meniscus; diplography; tendon